MIDLIFE CRISIS AND CONFLICT IN JOHN UPDIKE’S “SEPARATING” - Khatun, Mst. Rokeya (UC Journal: ELT, Linguistics and Literature Journal, 2025)
This paper analyzes midlife crisis and conflict, and their impact on familial relationships in John Updike's short story "Separating". Updike portrays the disintegration of a marriage through the portrayal of Richard and Joan Maple, a middle-aged couple, as they confront the emotional complexities which their impending separation imposes on their family dynamics. By intertwining both internal and external conflicts, Updike addresses love’s erosion, personal dissatisfaction, and societal transformation. Richard's inner conflicts—his struggle to accept the inevitability of the divorce, his emotional detachment, and his ambivalence toward his role as a father—reflect broader cultural and emotional shifts in mid-20th-century America, particularly the evolving perceptions of marriage and family structures. Employing a qualitative method, this research article examines how midlife crisis and conflict are represented in Updike's "Separating" within the sociocultural context of the time. This study, however, continues to make a significant contribution to world literature, offering future researchers valuable insights, ideas, and viewpoint on the writer and his works.